Pasting Characteristics of Composite Purple Sweet Potato and White Sweet Potato Flours - Rusdin Rauf; Rahmatika Nur Aini; N. Nurdiana (Journal of Nutraceuticals and Herbal Medicine, 2018)
Understanding the pasting characteristics of purple sweet potato (PS) and white sweet potato (WS) flours can provide clues about the product development direction. The purpose of the study was to evaluate the pasting characteristics of composite PS and WS flours. The research was conducted by making PS and WS flours. The flours are then mixed with variation ratios of 0:100, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, 90:10, and 100:0. All of the composite flours then tested the pasting characteristics. The data were tested using one-way anova and Duncan at a level of 0.05. The results indicated that there was the influence of composite ratios of WS flour and PS flour to pasting temperature, peak viscosity, hold viscosity, cold viscosityand reverse viscosity. However, there was no effect on the breakdown viscosity.